2012
DOI: 10.1007/s12098-012-0881-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Interventions to Prevent and Control Obesity Among Children and Adolescents: Its Applicability to India

Abstract: Childhood obesity is on the rise worldwide and its increasing prevalence in low and middle income countries is well-known. Obesity interventions have the potential to prevent adverse health outcomes; however, large gaps in research and knowledge about the efficacy and sustainability of such interventions remain. The objectives of this article were to review the evidence for interventions to prevent and control obesity among children and adolescents, evaluate their applicability in India, and discuss the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…To our knowledge, no previous study thus far has evaluated the school built environment as a potential target to promote physical activity in children in resource-limited settings. However, a recent review of 19 interventions to prevent obesity in low-income countries, including some that aimed to increase physical activity, found that the majority were effective in reducing body mass index, decreasing sedentary behaviors, and increasing physical activity [52]. Another study compared physical activity and sedentary behavior among school children from 34 countries and found that few engaged in sufficient physical activity according to country standards and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous study thus far has evaluated the school built environment as a potential target to promote physical activity in children in resource-limited settings. However, a recent review of 19 interventions to prevent obesity in low-income countries, including some that aimed to increase physical activity, found that the majority were effective in reducing body mass index, decreasing sedentary behaviors, and increasing physical activity [52]. Another study compared physical activity and sedentary behavior among school children from 34 countries and found that few engaged in sufficient physical activity according to country standards and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The variety of convenience foods available in the market and the role of media in sensitizing the parents and children to these changes could have also undoubtedly contributed to childhood obesity. [ 8 ] One of the factors that could significantly affect children's energy intake is the increasing availability of energy-dense, high-calorie foods/snacks and drinks in school canteens. Working mothers or single-parent families may also increase the demand for take away foods or increase the frequency of eating out and cause reliance on pre-prepared foods.…”
Section: Eterminants Of C Hildood mentioning
confidence: 99%
“…[ 12 ] Studies on prevention of childhood obesity focus primarily on this important issue as these sedentary activities are seen to have a direct correlation to increased body weight. [ 8 13 14 ] The Central Board of Secondary Education (CBSE) 2007 fact sheet[ 15 ] reported that only 30% of adolescents played regularly for at least 1 hour a day. Aggarwal et al .…”
Section: Eterminants Of C Hildood mentioning
confidence: 99%
“…A recent review of evidence of interventions for obesity that may be applied in Indian settings had very few studies from India, and it concluded that there are large gaps in knowledge about prevention and management of obesity. This review brings out the fact that there may be many interventions that are possible which need to be studied in India, while giving careful consideration to the various issues in study design such as feasibility and composition of interventions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%